Le genre de la réception - Laetitia Biscarrat (Communication)
The author presents the initial results of her exploratory research on how gender stereotypes in television series are understood, focusing on the workings of media reception. Data was collected in semi-structured interviews of students, an audience highly partial to serials. The results show that gender cuts across audience practices at all stages of reception. It permeates both the viewers’ horizons of expectation and their positioning during reception.